Tinjauan Kerusakan dan Analisis Ulang Tebal Perkerasan Menggunakan PCI dan Analisa Komponen - Putri, Weni Kasentari; Hermansyah, Hermansyah (Jurnal Ilmiah Rekayasa Sipil, 2023)
This study analyzes the road conditions in Sumbawa Regency and plans pavement solutions to address road damage. The data shows that there was no significant improvement in road conditions in 2020 compared to previous years. Good and fair road conditions only accounted for 69.29% of the total road length, while damaged and heavily damaged roads accounted for 6.57% and 24.14% respectively. Jalan Osapsio is one of the roads that has been damaged due to poorly maintained drainage. This research utilizes the Pavement Condition Index (PCI) method to assess the level of road damage and the Component Analysis method to design the pavement thickness. Based on the findings, several road segments exhibit different conditions. There are 13 segments with a Good rating and PCI values of 100 and 98, 1 segment with a Serious rating and a PCI value of 16, and 6 segments with a Failed rating and PCI values of 0. The segments with a Failed rating require urgent pavement reconstruction. Considering the PCI values, it is recommended to construct new pavement with appropriate thickness for the priority segments, namely a 6 cm thick Laston Surface Layer, a 20 cm thick Broken Stone Upper Base Layer, and a 15 cm thick Sirtu/Pitrum Lower Base Layer.This study provides an important contribution in understanding the road conditions in Sumbawa Regency and offers concrete solutions to address the road damage on Jalan Osapsio. The findings and research methodology are expected to serve as a reference for immediate improvements on Jalan Osapsio and provide insights for future research in Sumbawa Regency.